Kaleidoskopiske øjeblikke: Sanselighed og sammenhæng i det moderne mediebillede - Monefeldt Wittendorff, Nina (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2003)
We continually move about in various visual spaces and within these experience different accounts of what the world looks like. New stories about cultural diversity are created in the tension between mental and media-communicated pictures. Both old and new formations of meaning are set in motion and new forms of media affect our ways of navigating in the visual world. One of the ways to work with this is through the use of the kaleidoscope as a metaphor for how new contexts are made. The kaleidoscopic form appeals directly to the perceptive skills, which today points to a particular cultural competence that makes it possible to navigate in today’s media encounters. The main theoretical focus is based on modern affect theory, with the focus on the relationship between movement and moments.